(untitled) (NAU Journal of Library and Information Science, 2026)
This study examined demographic factors, library service quality and use of Electronic Information Resources (EIRs) by final-year law students in selected federal universities in South-West Nigeria. A survey research design was adopted, employing total enumeration of 552 final-year law students from the Federal University of Oye-Ekiti, the University of Ibadan, and the University of Lagos. Data were collected using a structured questionnaire comprising four sub-sections and using the Cronbach Alpha method: demographic characteristics (α = 0.83), EIR use (α = 0.88), and library service quality (α = 0.71). Out of 552 copies administered, 92.2% response rate were retrieved and found usable. Data were analysed using descriptive statistics, including frequency, percentage, mean, and standard deviation. Findings revealed that respondents were largely young adults, particularly those aged 26–35 years (30.1%).. Regarding EIR utilisation, Nigeria Weekly Law Report (80.7%), Law Pavilion (63.3%), and the library website (60.7%) were the most used resources, whereas -ROM (18.9 ) was the least used. espite the high usage of select resources, the overall frequency of EIR use was low (x = 1.94), falling below the criterion ean of 2.50. Si ilarly, perceived library service quality (x = 1.24) was slightly below the bench ar average (x = 2.46). The study concluded that although final-year law students in selected federal universities in South-West Nigeria, demonstrate awareness and selective use of key EIRs, the overall level of EIR utilisation and perceived library service quality remain below expected standards. Therefore, the study recommended strengthening awareness and training on EIRs, and high-quality library services should be prioritised.